Early clinical presentations and progression of calciphylaxis. (23rd April 2017) - Ghosh, Toshi; Winchester, Daniel S.; Davis, Mark D.P.; el‐Azhary, Rokea; Comfere, Nneka I.
Abstract: Background: Untreated calciphylaxis is a fatal disease of intra‐ and extravascular calcification, most commonly presenting in end‐stage renal disease (ESRD) patients. While early identification is critical for timely treatment, early‐stage clinical and histopathological descriptions have not, to our knowledge, been elucidated. As early clinical recognition is essential to prompt definitive histopathological diagnosis, this study describes a range of clinical and histopathological manifestations of early‐stage calciphylaxis. Methods: Five patients with clinical photographs of lesions of early‐phase calciphylaxis were chosen from a recent database of 101 patients. Their clinical histories were reviewed and correlated with their respective clinical and histopathological images of early‐stage disease and progression of the disease. Results: Two of the five patients were identified early to have calciphylaxis and were promptly initiated on aggressive, multimodal therapy, resulting in complete resolution and remission of calciphylaxis. The other three patients were also recognized in early stages, one without renal disease, although the disease had progressed to more advanced stages associated with greater morbidity and mortality. Conclusions: These cases demonstrate that calciphylaxis may be clinically misdiagnosed due to ill‐defined presentations, particularly in the early stages without the characteristic features of livedo racemosa and ulceration. However, recognition in the early stages is critical to implement timely treatment. As such, definitively diagnostic skin biopsy should be considered early in suspected cases to confirm the diagnosis of calciphylaxis and ensure prompt management of this lethal disease.